How do caregivers know when to take their child for immunizations? - Barker Lawrence E; Shaw Kate M (BMC, 2005)
Abstract Background Childhood vaccinations help reduce and eliminate many causes of morbidity and mortality among children. The objective of this study was to compare 4:3:1:3:3 (4+ doses of diphtheria and tetanus toxoids and pertussis vaccine, 3+ doses of poliovirus vaccine, 1+ doses of measles-containing vaccine, 3+ doses of Haemophilus influenzae type b vaccine, and 3+ doses of hepatitis B vaccine) coverage among children whose caregivers learned by different methods when their child's most recent immunization was needed. Methods Between July 2001 and December 2002, a portion of households receiving the National Immunization Survey were asked how they knew when to take the child in for his/her most recent immunization. Responses were post-coded into several categories: 'Doctor/nurse reminder at previous immunization visit', 'Shot card/record', 'Reminder/recall', and 'Other'. Respondents could give more than one answer. Children who did not receive any vaccines, had ≤ 1 visits for vaccinations, or whose caregiver did not provide an answer to the question were excluded from analyses. Chi-square analyses were used to compare 4:3:1:3:3 coverage among 19-35 month old children. Results Children whose caregivers indicated that a doctor/nurse told them at a previous immunization visit when to return for the next immunization had significantly greater 4:3:1:3:3 coverage than those who did not choose the response (77.2% vs. 70.1%, p < 0.01). However, no significant difference in coverage was found between households that did/did not indicate that reminder/recalls (71.0% vs. 75.5%, p = 0.24) helped them remember when to take their child for their most recent immunization visit; only borderline significance was found between those that did/did not choose shot cards (70.6% vs. 76.2%, p = 0.07). Conclusion A doctor or nurse's reminder during an immunization visit of the next scheduled immunization visit effectively encourages caregivers to bring children in for immunizations, providing an inexpensive and easy way to effectively increase immunization coverage.